THE PECULARITIES REMODELING CHAMBERS OF COR PULMONALE DEPENDING ON CENTRAL HEMODYNAMICS TYPES - Слабий, О.Б.; Гнатюк, М.С.; Гасюк, П.А. (World of Medicine and Biology, 2016)
Today of chronic cor pulmonale is an important medical and social problem due to the increasing chronic obstructive pulmonary disease, chronic pulmonary tuberculosis, professional lung pathologies. These diseases lead to arterial pulmonary hypertension, chronic cor pulmonale development and its decompensation. Pathogenesis of chronic cor pulmonale disease complicated and very versatile, which greatly complicates timely diagnosis of pulmonary arterial hypertension and chronic cor pulmonale. It is known that the structure and function of the heart affected and sound depends on several intracardial and extracardial factors (vegetative homeostasis, hemodynamic types) that can significantly influence the remodeling of the affected chambers of the heart, its complications and prognosis. Today there are three types of central hemodynamics: eukinetic, hypokinetic and hyperkinetic. It should specify what features remodeling of chronic cor pulmonale chambers, depending on the type of hemodynamics has not been fully studied.The aim of this work was to study the characteristics of remodeling of chronic cor pulmonale chambers for different types of central hemodynamics. Complex electrophysiological and morphological methods studied 46 heart mature white male rats that were divided into 4 groups. Group 1 included 12 intact animals, 2nd – rats with chronic cor pulmonale and eukinetic type of central hemodynamics, 3rd - 11 rats with chronic cor pulmonale and hypokinetic type of central hemodynamics, 4th - 15 experimental animals with chronic cor pulmonale and hyperkinetic type central hemodynamics. Postresektion arterial pulmonary hypertension and chronic cor pulmonale modeled in rats by performing right pulmonektomy. Operative interferences executed in the conditions of thiopental-natrium anesthesia with the observance of rules of aseptic and antiseptic. To set the type of central hemodynamics rheography performed and determined stroke volume, stroke index, minute volume of blood, total peripheral vascular resistance, cardiac index, which determined minute volume of blood ratio per unit body surface area. In determining the types of hemodynamic parameters into account received and especially the cardiac index, the most important of which is typical for hyperkinetic, the least - hypokinetic, medium - eukinetic type of central hemodynamics. After 3 months from the start of the experiment performed evtanasia animals bloodletting in the conditions of tiopental-natrium anesthesia. Removed the heart from the chest cavity and cut method G.G. Avtandilov and I.K.Jesypova conducted the separate chambers of the heart. Carried out individual weighing chambers of the heart, endocardial surfaces of plane geometry, volume measurements. Performed statistical analysis of the quantitative variables. Found that right pulmonektomiya led to the development of arterial pulmonary hypertension and chronic cor pulmonale characterized by uneven growth disproportionate weight of the heart chambers, their extension dominated hypertrophy and dilatation of the right ventricle. Obtained morphometric parameters show that the breach of relations between the masses of the heart chambers and their spatial characteristics of the most varied in the extreme types of hemodynamics (hypokinetic and hyperkinetic). It should also be noted that the expressed disturbances between masometry and spatial characteristics of heart chambers may lead to its dysfunction. The volumetric measurements of ventricular found that simulated experimental conditions expressed their growing prynosni and remote volumes and decreased back. Dominated with set changes in the right ventricle. After 3-months after the right pulmonektomy in animals with type eukinetic central hemodynamic reserve the right ventricle volume decreased by 23.2%, with hypokinetic - at 47.6%, while hyperkinetic - by 48.8% compared with the same control value. The largest extent reserve the right ventricle volume decreased after 3-month right pulmonektomy in experimental animals with extreme type of central hemodynamics (hypo- and hyperkinetic). Thus, this study and the results show that disbalance and disproporcional between the masses and spatial characteristics of chronic cor pulmonale chambers dominate by in the right ventricle at hypo- and hyperkinetic types of central hemodynamics.
Keywords: cor pulmonale; chambers; remodeling; central hemodynamics